Recommendations for Selection of Skincare Products Using the Promethee Method - Muhammad Aufa Zaydan Azfar; Sulistyo Dwi Sancoko (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2024)
This research aims to implement the Promethee method (Preference Ranking Organization Method for Enrichment Evaluation) in recommending appropriate skincare products based on facial skin type. With so many skincare products on the market, consumers may have difficulty choosing the right product. The Promethee method helps make multi-criteria decisions by considering various relevant factors such as skin type, price, user ratings, product quality, and price suitability based on the preferences of people who have used skincare products before as a reference in recommending skincare products. Recommendations are made based on data from the preferences of students who have used skincare products and provide an assessment of the products they have used. Researchers used the Promethee method as research to see how effective its use is in providing skincare product recommendations. The data used as a basis for manual calculations uses 10 data points for normal skin types. With the highest net flow value for normal skin types of 3.44444444 for Wardah Lightning and Ponds Men products. The highest net flow value for combination skin type is 24.250000, net flow for oily skin type is 14.222222, net flow for sensitive skin type is 14.722222, and net flow for dry skin type is 8.166667. The research results show that the Promethee method can provide appropriate recommendations regarding the selection of skincare products based on facial skin type.